Conceptualising modesty in a Muslimah magazine: A multimodal perspective / Syaheerah Roslee - Syaheerah, Roslee (2016)

(untitled)
This study attempts to firstly examine the textual representations of the concept of modesty in the articles of three sections in Eve magazine – Empowering Mindset, Muslim Women In Sports, and Exclusive Interview. Secondly, it examines the visual representations of the same concept. Lastly, it investigates the conceptualisationof modesty based on the representations mentioned previously. To fulfil the aims of this study, several strategies were adopted to examine the data. Textual wise, the representations were selected and analysed based on the reference to the verses in the Holy Quran with regards to the concept of modesty which is realised in terms of physical description and behavior. The analysis was verified by two coders in determining the portrayal of the concept in the textual representations. In terms of visuals, Kress and van Leeuwen’s (1996) framework on visual grammar was applied to identify the meaning of the visual representations in the texts with regard to modesty. Based on these representations, the conceptualisation of modesty was examined. The analysis of the textual representations reveals that the concept of modesty is realised in the three sections of Eve magazines through words like ‘hijab’, ‘veil’ or ‘scarfs’ found in the sections and based on the Quranic verse (24:31-32), these words are the references to modesty in terms of physical description or appearance. With reference to behavior, words like bold, sophisticated, vocal, and fashion savvy were found to describe Muslim women in the magazines. The visual analysis of the data discovers that symbolic process is the most frequently-found process in all the visuals in the three sections of Eve magazines. iv This is justifiable as the hijab that the Received Participants (RPs) or the Muslim women are wearing symbolizes modesty in Islam as they are used to cover one’s ‘awrah to guard their modesty. The visual and textual relisations of modesty eventually conceptualises modesty in Eve magazines. Evidence show that Eve magazine portrays modesty in a manner that is similar to what is stated in the Quran, yet elements of modernity has been injected to the Muslim women’s lifestyle as shown in the magzines. These elements influence them to modify the portrayal of modesty in their lives. This could suggest the identity of urban Muslim women whereby they portray modesty with a sense of modernity in their appearance and actions. In conclusion, this study hopes to provide valuable information for magazine producers when publishing for the different target readers so as to take into account religious and cultural issues with regard to the content of the magazines. It also hopes to facilitate English learning processes whereby visuals could be used in classrooms to discuss meanings they carry and the function of visuals in written texts should also be emphasized to enhance students’ visual literacy.